Mathematical Modelling: a teaching proposal for visually impaired students - Galvão, Lawrence Mota (2021)
We present the results of a pedagogical proposal based on Mathematical Modeling as a teaching strategy, in the inclusion of a visually impaired student, in the context of Education Technological, as well as addressing their contributions to the teaching and learning processes. The approach was designed for a visual impaired student based on Mathematical Modeling as main teaching strategy. The qualitative reasearch was conducted through a study of case. The results points that the Mathematical Modeling used as a teaching strategy of Mathematics learning: a) provides greater autonomy and inclusion of visually impaired students; b) empowers the re-examination of mathematical knowledge and its application in daily problem situations; c) allows the creation of mental and non-mental Mathematical Models.